DESIGN AND CHARACTERIZATION OF A BILAYER SODIUM ALGINATE/CARBOXYMETHYL CELLULOSE PATCH ENRICHED WITH CANNABIDIOL AND ACTIVATED CARBON FOR POTENTIAL USE IN ACNE TREATMENT - Velandia Paris, Maria Angelica; León Ávila, Emerson Eliecer; Garzón , Hector David (Journal of the Chilean Chemical Society, 2025)
This research explores the use of natural polymers as a sustainable alternative to synthetic polymers for developing patches with diverse applications. We created a bilayer patch utilizing sodium alginate (SA) and carboxymethylcellulose (CMC) as natural polymers. Each layer contained an active ingredient: cannabidiol (CBD) in the SA layer and activated carbon (AC) in the CMC layer. CBD and AC were chosen due to their potential as natural treatments for skin conditions like acne. The SA layer was formed using ionic gelation, while the CMC layer was created through compression, both considered eco-friendly methods. The mechanical properties of the patch were evaluated, showing the SA layer had a breaking strength of 11.617 N ± 0.2839, and the CMC layer had a strength of 12.36 N ± 0.1300. Both layers exhibited effective swelling capacity for exudate containment, with swelling percentages of 75.78% ± 1.120 for SA and 76.84% ± 1.171 for CMC. The morphology of the layers met expectations. To quantify the amount of CBD in the patch, high-performance liquid chromatography was employed, optimizing separation conditions based on the column used. The analysis revealed that the SA layer contained 2.08 mg of CBD. The analytical method proved accurate for quantifying CBD in various patch samples. In summary, the developed bilayer patch, using natural materials and sustainable techniques, presents a viable alternative to conventional acne treatments. It demonstrates suitable mechanical properties and effective CBD release, aligning with greener and more sustainable practices.